PENGARUH KONSENTRASI PUPUK ORGANIK CAIR (POC) TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS TANAMAN KEDELAI (Glycine max (L.) Merill) - Lalu Fauzan Walid; Susylowati Susylowati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
The aim of this research was to study effect and the best dose of liquid organic fertilizing (LOF) on soybean varieties yield and the most suitable varieties cultivated on East Borneo in general.The experiment was conducted from August to November 2013 in agricultural land of Sukorejo farmer group, Lempake Village, SamarindaUlu District, Samarinda Town. The experiment design that used is Split Plot Design 3x4 with 3 replication. As the main plot is Anjasmoro (v1), Burangrang (v2), dan Argomulyo (v3). As the subplot is the concentration of liquid organic fertilizer consisting of 4 levels in 0 mL L-1 water (k0), 2 mL L-1 water (k1), 4 mL L-1 water (k2), 6 mL L-1 water (k3). The data were analyzed using analysis of variance. If there is a real effect then followed by LSD test to compare the 5% average of two treatment. Result of the analysis of variance showed that treatment significantly affected all varieties of variable observations except days to flowering, number of pods and dry weight of pods. Liquid organic fertilizing (LOF) treatment effect was not significant on all variables observations except age crop, the total number of pods, seed dry weight on plot, seed dry weight on hectare. Argomulyo varieties showed the best results with a concentration of 4 mL L-1 water of liquid organic fertilizing (LOF).